Single-Molecule Tracking of Inositol Trisphosphate Receptors Reveals Different Motilities and Distributions - Smith, Ian F. (The Biophysical Society, 2014)
Puffs are local Ca(2+) signals that arise by Ca(2+) liberation from the endoplasmic reticulum through the concerted opening of tightly clustered inositol trisphosphate receptors/channels (IP(3)Rs). The locations of puff sites observed by Ca(2+) imaging remain static over several minutes, whereas fluorescence recovery after photobleaching (FRAP) experiments employing overexpression of fluorescently tagged IP(3)Rs have shown that the majority of IP(3)Rs are freely motile. To address this discrepancy, we applied single-molecule imaging to locate and track type 1 IP(3)Rs tagged with a photoswitchable fluorescent protein and expressed in COS-7 cells. We found that ∼70% of the IP(3)R1 molecules were freely motile, undergoing random walk motility with an apparent diffusion coefficient of ∼0.095 μm s(−1), whereas the remaining molecules were essentially immotile. A fraction of the immotile IP(3)Rs were organized in clusters, with dimensions (a few hundred nanometers across) comparable to those previously estimated for the IP(3)R clusters underlying functional puff sites. No short-term (seconds) changes in overall motility or in clustering of immotile IP(3)Rs were apparent following activation of IP(3)/Ca(2+) signaling. We conclude that stable clusters of small numbers of immotile IP(3)Rs may underlie local Ca(2+) release sites, whereas the more numerous motile IP(3)Rs appear to be functionally silent.